A novel compound heterozygous mutation of the gene in a patient with autoimmune polyendocrine syndrome type 1 - Junghwan Suh; Han Saem Choi; Ahreum Kwon; Hyun Wook Chae; Jin-Sung Lee; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2019)
Autoimmune polyendocrine syndrome type 1 (APS-1), or autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy is a rare, autosomal recessive autoimmune disease caused by a mutation of the autoimmune regulator (AIRE) gene. The main symptom triad in APS-1 comprises chronic mucocutaneous candidiasis, adrenal insufficiency, and hypoparathyroidism. Various autoimmune diseases and ectodermal abnormalities are also commonly associated with the syndrome. The treatment of APS-1 includes hormone replacement and symptom control. It is important to monitor such patients for clinical manifestations of their disease through regular follow-up. We report the case of a 10-year-old Korean girl with APS-1 due to a novel compound heterozygous mutation of the AIRE gene. This patient's main clinical manifestations were adrenal insufficiency and chronic mucocutaneous candidiasis. The patient had a previously known pathogenic variant of c.1513delG (p.Ala505ProfsTer16), and a newly discovered variant of c.1360dupC (p.His454ProfsTer50).